2022
DOI: 10.1021/acs.est.1c05841
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electron Transfer Coordinated by Oxygen Vacancies Boosts Selective Nitrate Reduction to N2 on a Co–CuOx Electroactive Filter

Abstract: Atomic hydrogen (H*) is used as an important mediator for electrochemical nitrate reduction; however, the Faradaic efficiency (FE) and selective reduction to N2 are likely compromised due to the side reactions (e.g., ammonia generation and hydrogen evolution reactions). This work reports a Co–CuO x electrochemical filter with CoO x nanoclusters rooted on vertically aligned CuO x nanowalls for selective nitrate reduction to N2, utilizing the direct electron transfer between oxygen vacancies and nitrate to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Recent studies revealed that electrocatalytic NO 3 – reduction can occur via both direct electron transfer and/or atomic H*-mediated indirect reduction pathways. , During the electrochemical reduction of NO 3 – in aqueous media, protons were reduced to generate atomic H*, which could break the N–O bond and could be used as a reducing agent for NO 3 – . EPR was used to identify the formation of H* with 5,5-dimethyl-1-pyrroline- N -oxide (DMPO) as a radical trapping reagent .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed that electrocatalytic NO 3 – reduction can occur via both direct electron transfer and/or atomic H*-mediated indirect reduction pathways. , During the electrochemical reduction of NO 3 – in aqueous media, protons were reduced to generate atomic H*, which could break the N–O bond and could be used as a reducing agent for NO 3 – . EPR was used to identify the formation of H* with 5,5-dimethyl-1-pyrroline- N -oxide (DMPO) as a radical trapping reagent .…”
Section: Resultsmentioning
confidence: 99%
“…As oxidative radicals, such as superoxide and hydroxyl radicals can only be produced at the cathode under aerobic condition or at the anode, , the C-F bond breakage could be attributed to either direct or indirect electrochemical reduction in this study. The electrochemical reduction mechanisms involved direct electron transfer and indirect reduction via atomic H*. , The atomic H* involved in the electroreduction process was detected by the electron paramagnetic resonance (EPR) spin trapping. As shown in Figure S6, nine characteristic peaks of DMPO-H signal of atomic H* trapped by DMPO were detected at both OTAB-modified carbon paper cathode and pure carbon paper cathode.…”
Section: Resultsmentioning
confidence: 99%
“…More accessible reactive sites in the catalyst indicate higher catalytic activity in the GOR. The following research on electrochemical analysis is normalized by the ECSA. …”
Section: Resultsmentioning
confidence: 99%